ABOUT THE INTERFERENCES INFLUENCE IN THE SIGNAL OF A GLIDESLOPE RADIO BEACON SYSTEM ON THE ACCURACY OF THE AUTOMATIC APPROACH FOR LANDING OF THE PLANE - Полухін, Анатолій Васильович; Закалата, Дарина Юріївна; Ляховський, Васіліос (Science-based technologies, 2019)
Flight safety assurance is an urgent and at the same time complex problem. Its complexity lies in the fact that the level of flight safety is determined by many factors that manifest themselves at all stages of the aircraft’s life cycle. The main factors that significantly affect the level of flight safety include: the state of aviation equipment (technical factor), the correctness of the aviation personnel actions (human factor), the state of the environment in which the operation of aviation equipment occurs, and others. Statistics shows that about 36% of all accidents in the world’s air transport occur at the stages of approach and landing, because they are characterized by significant changes in speed, altitude, heading of the aircraft, the modes of engines operation, a change in configuration from flight- to landing- in conditions of psychological pressure on the crew the following factors: proximity to the earth and a small margin of speed and lack of time to analyze the situation and make decisions as to aircraft operation. The level of flight safety during the approach of an aircraft by a glide path beacon system signal, together with other technical factors, is affected by the accuracy of glide path “capture” and the accuracy of movement along it from the point of view that the signal contains static and dynamic noise. To conduct a study of the dynamic noise influence in the signal of a glide path beacon system on the accuracy of an aircraft's automatic approach, the authors of the article developed a digital mathematical model of the flight dynamics of a medium-haul aircraft, that allows to study the processes of its stabilization at a given holding zone altitude while extending flaps into landing position before entering the glide path, "capture" the glide path and stabilizing the aircraft on it in the absence or presence of interference in the signal of glide path beacon system. The influence of the low-frequency and high-frequency interference on the glide path of a glide path beacon system on the maximum intensity provided for by regulatory documents on the accuracy of the automatic approach of an aircraft has been studied. It has been shown that the specified interference has an insignificant effect on the aircraft’s trajectory parameters, but causes it to “swing” in pitch and vertical acceleration with amplitudes that increase as the aircraft approaches the glide path beacon, while remaining within the limits allowed by regulatory documents.